PENGGUNAAN METODE PROBLEM BASED INSTRUCTION (PBI) UNTUK MENINGKATKAN HASIL BELAJAR DAN MOTIVASI SISWA PADA MATERI PENGUKURAN NILAI RESISTOR KELAS X DI SMK NEGERI 1 DARUL KAMAL ACEH BESAR - Yulidatullah, Yulidatullah; Silahuddin, Silahuddin; Sadrina, Sadrina (CIRCUIT: Jurnal Ilmiah Pendidikan Teknik Elektro, 2018)
Based on the observations made in class X SMK 1 Darul Kamal Electronics Aceh Besar shows the system applied learning in SMK 1 Darul Kamal Aceh Besar, is dominated by conventional learning. So active students tend to be passive because they only receive the material and exercises from the teacher, so in the learning process of students do not understand the material given by teachers and students also feel tired and boring. One alternative to solve these problems, the researchers tried to offer a study which emphasizes the students learning activities in a group that is using the learning method PBI. The purpose of this study was to determine the increase in student motivation after following study with PBI teaching methods. The research was conducted on November 13 until November 15, 2017. The design of this study research design real experiments. The population in this study are all students of SMK 1 Darul Kamal, amounting to 198 students, while the sample in this study were students of class X Electronics amounting to 22 students. The data collection technique used observation and motivation questionnaire. Results showed significant improvements observation using the first RPP, RPP RPP II and III, both observation ability of teachers to manage learning and student activity observation. The results of observations of teachers at the first meeting with a total value of 80.62%, in the second meeting with a value of 81.85% and the third meeting of the results has been rising by up to 85%. So also with the results of the student activity observation of the value of 76.42% to 79.28%, even increased by 84.28%. The results using motivational angkket shows the average value of the experimental class was 87.4%. the results of students motivation increased class. Based on these results it can be concluded that the use of PBI learning methods can increase student motivation in the matter "resistor value measurement" in class X SMK 1 Darul Kamal Electronics Aceh Besar.